IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SD/MI - Lesta Septia Sari; Jonata; Putri Handayani (Journal of Innovation Research and Knowledge, 2022)
Purpose: Design/methodology/approach: . This study aims to improve critical thinking skills through the application of the Problem Based Learning contoh based on local wisdom. This research is aclassroom action research conducted in dua cycles with the stages of planning, implementing, observing, and reflecting. The data collection instruments used question instruments, observation sheets, documentation, and field notes. The research subjects were fourth grade students of Junior High School 15 Tempilang. Findings: The results showed an increase in critical thinking skills as indicated by the data in the pre-cycle by 41%, in cycle I increased 68.18%, and in cycle II increased by 81.81%. Increasing critical thinking skills also has an impact on the completeness of student learning outcomes. This is indicated by the completeness of learning outcomes on the Indonesian language content in pre-cycle, cycle I, and cycle II respectively, namely 41%, 68%, and 86%. Furthermore, the IPS content in pre-cycle, cycle I, and cycle II respectively were 25%, 68%, and 86%.